High Resolution Optical Spectral Image of the Singlet and Triplet States of Dibenzanthracene in Polymethylmethacrylate - Bayrakceken, Fuat (Asian Journal of Chemistry, 2012)
Highly sensitive detection of singlet-singlet, triplet-triplet optical absorptions and delayed fluorescence of 1,2:5,6-dibenzanthracene in polymethylmethacrylate were experimentally observed by flash and laser flash photolysis techniques. 1,2:5,6-Dibenzanthracene molecules were excited in a two-step process. In the first step the excited singlets are created by optical pumping, which undergoes intersystem crossing to triplet state, then triplet-triplet absorption creates an excited triplet 1,2:5,6-dibenzanthracene molecule which returns to the first excited singlet level by intersystem crossing. The re-created first excited singlet of 1,2:5,6- dibenzanthracene decays back to the ground state by emitting B-type of delayed fluorescence, which was observed at the same emission band of normal fluorescence.